Revisiting pedagogical skills: A comprehensive analysis of Mathematics teaching competencies among elementary educators - Salamah, Salamah (Jurnal Cakrawala Pendidikan, 2024)
This research aims to explore the intricate relationships between attitudes towards the teaching profession, teaching experience, self-concept, and teaching competencies among elementary school teachers. The study’s sample comprises 40 first-grade teachers from elementary schools in Yogyakarta, selected through a multistage cluster random sampling technique. The findings of this research indicate several key correlations: (1) a positive correlation exists between attitudes towards the teaching profession and teaching competencies; (2) teaching experience positively correlates with teaching competencies; (3) self-concept also shows a positive correlation with teaching competencies. Moreover, the study reveals that attitudes towards the teaching profession, teaching experience, and self-concept collectively contribute to a significant positive correlation with teaching competencies. These results highlight the multifaceted nature of teaching proficiency and underscore the importance of fostering positive attitudes, accumulating teaching experience, and developing a strong self-concept to enhance educational outcomes in elementary education.